Extracorporeal cardiopulmonary resuscitation for sudden cardiac arrest induced by septic shock-related adrenal crisis - Martin Pažitný; Matúš Maruniak; Martin Ilenin; Dušan Rybár; Tomáš Grendel (Turkish Journal of Emergency Medicine)
Extracorporeal cardiopulmonary resuscitation is being increasingly used to treat refractory in-hospital cardiac arrest (IHCA). Etiologies of IHCA may differ from etiologies of out-of-hospital cardiac arrest. We report a case of a 50-year-old man who was admitted to a local hospital, presenting with drowsiness, hypotension, and severe metabolic acidosis. After being transferred to our tertiary center, he quickly progressed to cardiac arrest and required extracorporeal cardiopulmonary resuscitation (eCPR) with veno-arterial extracorporeal membrane oxygenation (VA ECMO). Initially, due to high levels of inflammatory markers, sepsis became the most probable diagnosis. The patient responded well to antibiotics and supplemental corticosteroid therapy. Subsequent investigation revealed sepsis-induced absence of cortisol based on previously unknown hypopituitarism. Following corticoid administration, rapid myocardial recovery occurred with successful ECMO weaning. The patient was discharged from the ICU after 13 days with a favorable neurological outcome. Therefore, VA ECMO seems to be a feasible method to provide a bridge to recovery in patients with sudden hemodynamic collapse due to an adrenal crisis.